Association between thyroid-stimulating hormone and maternal hemodynamics in hypertensive disorders of pregnancy: an observational study - Yu Liu; Bo Gao; Xin Zeng; Jing Yang; Lei Zhang; Ganwei Xu; Ruizhe Jia; Zhengfeng Xu (BMC, 2019)
Abstract Background Hypertensive disorders of pregnancy (HDP) are characterized by hemodynamic disturbances. Altered thyroid function is a risk factor for poor outcomes of pregnancy. However, the associations between thyroid function biomarkers and maternal hemodynamics during pregnancy in HDP remain unclear. Methods From January 2016 to January 2018, pregnant women diagnosed with HDP admitted to the Nanjing Maternity and Child Health Care Hospital were prospectively enrolled in the third trimester. Normally distributed variables were expressed as mean ± standard deviation and skewed variables were expressed as median (25th percentile, 75th percentile). Correlations between thyroid-stimulating hormone (TSH) or free thyroxine (FT4) and maternal hemodynamic parameters were assessed by Pearson's correlation coefficient and 95% confidence interval (95%CI). Bonferroni's correction for multiple correlations was performed. Logistic regression models with odd ratio (OR) and 95%CI were applied to confirm the associations. Results A total of 163 third-trimester pregnant women with HDP with a mean gestational age of 35.62 ± 2.83 weeks were recruited. The infant birth weight of patients with elevated TSH levels was lower than that of patients with normal TSH levels (2635 ± 867 g vs. 3037 ± 673 g, p = 0.002). Reduced cardiac output (CO) was defined as CO < 3.5 L/min. The infant birth weight of patients with reduced CO was lower than that of patients with normal CO (2250 ± 510 g vs. 2890 ± 774 g, p = 0.002). TSH levels were significantly and negatively correlated with CO (r = − 0.260, 95%CI: − 0.392- -0.103, p < 0.001). FT4 levels were not significantly correlated with any of the maternal hemodynamic parameters (all p > 0.05). TSH level (OR = 1.371, 95%CI: 1.086-1.733, p = 0.008) was confirmed associated with reduced CO in the logistic regression analysis. Conclusions Elevated TSH levels are associated with reduced CO in HDP during the third trimester.